Efficiency of purification methods on the recovery of exopolysaccharides from fermentation media - Pintado, Ana. I.E.; Ferreira, José A.; Pintado, Manuela M.E.; Gomes, Ana M.P.; Malcata, F. Xavier; Coimbra, Manuel A. (Carbohydrate polymers, 2020)
•MRS medium is the major source of interfering compounds.•MRS medium was responsible for the introduction of glucose-rich material.•Lactose may promote the co-precipitation of several medium components.•YE also contributed with mannoproteins.•TCA method was shown to be more efficient in recovery of EPS. De-Man Rogosa and Sharpe (MRS) is a complex medium commonly used to obtain exopolysaccharides (EPS) from lactic acid bacteria. However, the various nutrients (carbon and nitrogen sources) of media and supplements added to enhance the bacterial growth and EPS production, may interfere with the purification of the extracts resulting in an over-estimation of the EPS and erroneous structural assignments. The efficiency of trichloroacetic acid (TCA)/pronase and 5-sulfosalicylic acid – SSA methods was evaluated. In addition, the interference of the major MRS broth components as well as lactose was evaluated using xanthan gum as model control EPS. It was concluded that MRS medium is a major source of interfering compounds in the quantification of EPS, mainly glucose-rich material and to a lesser extent mannoproteins from yeast extract. This effect was found to be potentiated by the presence of lactose. TCA/pronase method was shown to be more efficient in eliminating interferents.